E-Learning Tri-N Based Interactive to Improve Student Learning Motivation in Statistics Learning - Pramudianti, Tiara; Widodo, Sri Adi; Hidayat, Wahyu; Sulistyowati, Fitria; Arifin, Usman (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to develop an interactive learning media based on e-learning using Google Sites with the Tri-N approach (Niteni, Nirokake, Nambahi) to enhance students' learning motivation in the Statistics material for eighth-grade junior high school students. The research method employed is Research and Development (R&D) using the 4D development model, consisting of the Define, Design, Develop, and Disseminate stages. Data were collected through initial needs observation and product validation by media and material experts. The product developed is an interactive e-learning media containing teaching materials, instructional videos, practice exercises, and assessments based on the Kurikulum Merdeka. This media is designed to facilitate students' learning activities through the stages of Niteni, Nirokake, and Nambahi, with the expectation of encouraging active participation in the learning process. Due to time limitations, this research was conducted only up to the expert validation stage; practicality and effectiveness tests were not carried out. The validation results indicate that the Tri-N-based e-learning media is suitable for use in Statistics learning. In the future, this media has the potential to be further developed for other materials and educational levels as an innovative digital learning alternative for teachers and students.